Legal Reconstruction Return on Assets In Money Laundering Crimes In the Department of Justice Value-Based Forestry - Safrin Ritonga; Anis Mashdurohatun; Sri Endah Wahyuningsih (International Journal Reglement & Society (IJRS), 2023)
In the current Money Laundering Act of the Ministry of Forestry and to find the reconstruction of the Asset Recovery Law In The Crime Of Money Laundering In The Department Of Forestry Based On The Value Of Justice. Asset Recovery in Money Laundering Crimes in the Ministry of Forestry Has Not Been Based on the Value of Justice, because the phrase